Why German farmers have their animals vaccinated against Bluetongue virus serotype 8: Results of a questionnaire survey. Issue 1 (1st January 2015) - Gethmann, J.; Zilow, V.; Probst, C.; Elbers, A.R.W.; Conraths, F.J.
Abstract In response to the Bluetongue disease epidemic in 2006–2007, Germany started in 2008 a country-wide mandatory vaccination campaign. By 2009 the number of new outbreaks had decreased so that vaccination became voluntary in 2010. We conducted a questionnaire survey in cattle and sheep farms in three German federal states, namely North-Rhine Westphalia, Rhineland Palatinate and Saxony-Anhalt to estimate the vaccination uptake in 2010, the intention to vaccinate in 2011 and the main determinants of refusal or acceptance to do so. The results showed that 42.8% (40.6–45.1) of the cattle farmers and 33.8% (31.8–35.8) of the sheep farmers had their animals vaccinated in 2010, whereas 40.7% (38.5–43.0) of cattle and 37.93% (35.8–40.1) sheep farmers expressed their intention to vaccinate in 2011. The main reasons mentioned for having animals vaccinated against BTV-8 were ability to export animals, prevention of production losses, subsidized vaccination, and recommendation by the veterinarian. Motives for refusing vaccination were presumed low risk of infection, costs, absence of clinical BT symptoms, presumed negative cost-benefit ratio, and negative experience with previous vaccination events (side effects). We assume that in order to increase farmers' motivation to have their animals immunized against BTV-8, (1) the vaccination needs to be subsidized, (2) combined vaccines with several different BT serotypes or even other diseases should be available and (3) farmers need to be better informed about the safety and benefit of vaccination.